Project Management Maturity Strategies: A Case Study Approach - Georgi, John / J.G (2017)
Project management (PM) has gone through several evolutionary stages and has now been recognised as a strategic management method. Over the last two decades the PM community has been developing viable methods to assess and improve PM capability in organisations, which brought about different maturity models. This research used the P3M3 maturity model in light of arguments of fit and contingency theory. Based on a cross-case analysis, this research systematically analysed two organisations using the P3M3 model and semi structured interviews. The research follows a logical and systematic process to evaluate an appropriate level of maturity for an organisation’s context. The process includes: identify current level of maturity, identify appropriate level, and finally evaluate the benefits and costs of the gap. This research concluded that there is a strong need to develop a quantitative/economic method to apply the steps identified, rather than a qualitative approach that may be inaccurate or biased.